Curable hard coat resin composition, cured product and laminate

The curable hard coat resin composition addresses the issues of high moisture permeability and low hardness in conventional compositions by using an epoxy compound with a polyalicyclic structure and poly(meth)acrylate, achieving low moisture permeability and high hardness for applications like barrier films and polarizing plates.

JP7615816B2Active Publication Date: 2025-01-17ARAKAWA CHEM IND LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021050535
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-01-17
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

Conventional hard coat resin compositions for polarizing plates in liquid crystal display devices suffer from high moisture permeability and insufficient hardness, leading to display unevenness due to humidity changes in the environment.

Method used

A curable hard coat resin composition comprising an epoxy compound with a specific polyalicyclic structure, poly(meth)acrylate with three or more (meth)acryloyl groups, and a photoradical initiator, along with optional components like a photoacid generator, (meth)acrylate with two or less (meth)acryloyl groups, inorganic particles, and organic solvents, to achieve low moisture permeability and high hardness.

Benefits of technology

The composition provides a cured product with low moisture permeability and excellent hardness, suitable for applications such as barrier films, polarizing plates, and organic EL device sealing materials, maintaining stability under varying humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615816000001
    Figure 0007615816000001
  • Figure 0007615816000002
    Figure 0007615816000002
  • Figure 0007615816000003
    Figure 0007615816000003
Patent Text Reader

Abstract

To provide a curable resin composition for a hard coat which gives a cured product having low moisture permeability and high hardness.SOLUTION: There are provided: a curable resin composition for a hard coat which contains a polyalicyclic epoxy compound represented by a specific formula and / or a derivative thereof (A), a poly(meth)acrylate (B) having three or more (meth)acryloyl groups, and a photoradical initiator (C); a cured product of the resin composition; and a laminate having the cured product on at least one surface of a substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for curable hard coat, a cured product, and a laminate. [Background technology]

[0002] Conventionally, polarizing plates used in liquid crystal display devices are manufactured by adsorbing iodine or the like onto a polyvinyl alcohol film, and laminating triacetyl cellulose (TAC) films onto both sides of a polarizer oriented by stretching or the like. A transparent curable hard coat resin composition is applied to the surface of the TAC film, and cured to form a high-hardness coating (hard coat layer), which provides scratch prevention function. As such a resin composition, for example, one using a multifunctional urethane (meth)acrylate or the like is known (Patent Document 1).

[0003] However, since TAC film is highly hygroscopic (has high moisture permeability), depending on the usage environment, humidity can cause it to expand and contract, which can lead to display unevenness and the like.

[0004] As a technique for solving the moisture permeability problem, a resin composition containing a (meth)acrylate compound having an alicyclic hydrocarbon skeleton, a cyclic (meth)acrylate compound, and a polymerization initiator is known (Patent Document 2). However, when the (meth)acrylate compound is used, although low moisture permeability is exhibited, the hardness is low and it is insufficient as a hard coat agent. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-290491 [Patent Document 2] International Publication No. 2014 / 157668 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a curable resin composition for hard coats which gives a cured product having low moisture permeability and high hardness. [Means for solving the problem]

[0007] The present inventors have conducted extensive research and found that a resin composition essentially containing an epoxy compound having a specific polyalicyclic structure or a derivative thereof can solve the above problems, and have completed the present invention. That is, the present invention relates to the following curable hard coat resin composition, cured product, and laminate.

[0008] 1. Epoxy represented by general formula (1) transformation (A) a compound and / or a derivative thereof, (B) a poly(meth)acrylate having three or more (meth)acryloyl groups, and (C) a photoradical initiator. fruit, The derivative is any one of an α,β-unsaturated carboxylic acid adduct of the epoxy compound, a (meth)acrylate adduct having a hydroxy group of the epoxy compound, and a urethane (meth)acrylate of the epoxy compound. A curable resin composition for hard coats. [ka] (In formula (1), the dashed lines represent no bond or a carbon-carbon-carbon bond.)

[0009] 2. The curable hard coat resin composition according to item 1 above, wherein component (B) comprises at least one member selected from the group consisting of pentaerythritol poly(meth)acrylate, dipentaerythritol poly(meth)acrylate, and tripentaerythritol poly(meth)acrylate.

[0010] 3. The curable hard coat resin composition according to item 1 or 2 above, wherein the ratio of the components (A) and (B) used is (A) / (B)=10 / 90 to 90 / 10 by weight of solids.

[0011] 4. The curable hard coat resin composition according to any one of items 1 to 3 above, further comprising a photoacid generator (D).

[0012] 5. The curable hard coat resin composition according to any one of items 1 to 4 above, further comprising a (meth)acrylate (E) having two or less (meth)acryloyl groups.

[0013] 6. The resin composition for curable hard coat according to any one of items 1 to 5 above, further comprising inorganic particles (F).

[0014] 7. A cured product of the resin composition for curable hard coat according to any one of items 1 to 6 above.

[0015] 8. A laminate having the cured product according to item 7 above on at least one surface of a substrate. Effect of the Invention

[0016] The curable hard coat resin composition according to the present invention provides a cured product having low moisture permeability and excellent hardness. The cured product has low moisture permeability and is therefore applicable to applications such as barrier films, polarizing plates, sealing materials for organic electroluminescence devices, and packaging films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The curable hard coat resin composition of the present invention is an epoxy compound represented by the general formula (1). transformation The composition contains a compound and / or a derivative thereof (A) (hereinafter referred to as component (A)), a poly(meth)acrylate having three or more (meth)acryloyl groups (B) (hereinafter referred to as component (B)), and a photoradical initiator (C) (hereinafter referred to as component (C)). Note that (meth)acryloyl means methacryloyl or acryloyl, and (meth)acrylate means methacrylate or acrylate (hereinafter the same).

[0018] [ka] (In formula (1), the dashed lines represent no bond or a carbon-carbon-carbon bond.)

[0019] The epoxy compound represented by the general formula (1) has a polycyclic structure, so that the cured product of the resin composition exhibits low moisture permeability. In addition, since it has epoxy structures at both ends, it can be derivatized in various ways.

[0020] Commercially available epoxy compounds include the compounds of the following formula (2) (trade name: "DE-103", manufactured by ENEOS Corporation) and (3) (trade name: "DE-102", manufactured by ENEOS Corporation).

[0021] [ka]

[0022] [ka]

[0023] Examples of the derivative of the epoxy compound represented by general formula (1) include an α,β-unsaturated carboxylic acid adduct of the epoxy compound (hereinafter also simply referred to as an acid adduct), a (meth)acrylate adduct having a hydroxy group of the epoxy compound (hereinafter also simply referred to as a (meth)acrylate adduct), and a urethane (meth)acrylate of the epoxy compound (hereinafter also simply referred to as a urethane (meth)acrylate).

[0024] (α,β-unsaturated carboxylic acid adduct of the epoxy compound) Examples of α,β-unsaturated carboxylic acids include α,β-unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid; and α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid. In addition, salts of α,β-unsaturated carboxylic acids may be used, and examples of the salts include alkali metal salts such as sodium salts and potassium salts; and ammonium salts with ammonia, methylamine, ethanolamine, and the like. These may be used alone or in combination of two or more. Among them, α,β-unsaturated monocarboxylic acids are preferred, and (meth)acrylic acid is more preferred. Incidentally, (meth)acrylic means methallyl or acrylic (similar below).

[0025] The amount of α,β-unsaturated carboxylic acid used is usually 0.8 to 2.5 moles, and preferably 0.9 to 2.0 moles of carboxyl groups (COOH) per mole of epoxy groups in the epoxy compound represented by general formula (1).

[0026] The acid adduct can be obtained by adding an epoxy compound of general formula (1) to an α,β-unsaturated carboxylic acid. The reaction conditions are not particularly limited, and for example, the reaction temperature is usually about 60 to 120°C (preferably about 80 to 110°C) and the reaction time is about 4 to 10 hours (preferably about 6 to 8 hours).

[0027] In the production of the acid adduct, an organic solvent may further be used. Examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, isooctane, and n-decane; alicyclic hydrocarbons such as cyclohexane; esters such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, cyclohexanone, and methylcyclohexanone; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether; and alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, and t-butanol. The amount of the organic solvent used is preferably adjusted so that the concentration of the reaction solution is 40 to 70% by weight.

[0028] (Regarding the (meth)acrylate adduct having a hydroxy group of the epoxy compound) Examples of the (meth)acrylate having a hydroxy group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate; dihydroxyalkyl (meth)acrylates such as 2,3-dihydroxypropyl (meth)acrylate, 3,4-dihydroxybutyl (meth)acrylate, glycerin mono(meth)acrylate, and 1,4-dihydroxyheptyl (meth)acrylate; cycloalkyl mono(meth)acrylates such as 1,4-cyclohexanedimethanol mono(meth)acrylate and adamantyl mono(meth)acrylate; Mono(meth)acrylates having a hydroxy group and an ether bond, such as 2-hydroxy-3-phenoxypropyl(meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate; Erythritol (meth)acrylates such as erythritol di(meth)acrylate and erythritol tri(meth)acrylate; pentaerythritol (meth)acrylates such as pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, and pentaerythritol tri(meth)acrylate; dipentaerythritol (meth)acrylates such as dipentaerythritol mono(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and dipentaerythritol penta(meth)acrylate; Examples of the tripentaerythritol (meth)acrylates include tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, and tripentaerythritol hepta(meth)acrylate. These may be used alone or in combination of two or more. Among them, pentaerythritol (meth)acrylates and dipentaerythritol (meth)acrylates are preferred because they increase the hardness of the cured product.

[0029] The (meth)acrylate having a hydroxyl group may be a mixture containing a poly(meth)acrylate not having a hydroxyl group. Examples of poly(meth)acrylate not having a hydroxyl group include erythritol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and tripentaerythritol octa(meth)acrylate. The content of poly(meth)acrylate not having a hydroxyl group is 70% by weight or less relative to the total weight ratio of the (meth)acrylate having a hydroxyl group and the (meth)acrylate not having a hydroxyl group being 100% by weight.

[0030] Examples of commercially available (meth)acrylates having a hydroxy group include "Aronix M305", "Aronix M306", "Aronix M400", "Aronix M402", "Aronix M403", "Aronix M404", "Aronix M405", and "Aronix M406" (manufactured by Toagosei Co., Ltd.), "KAYARAD DPHA" (manufactured by Nippon Kayaku Co., Ltd.), "NK Ester A-9550", "NK Ester A-DPH", and "NK Ester A-TMM-3L" (manufactured by Shin-Nakamura Chemical Co., Ltd.), "Viscoat #300", "Viscoat #802" (manufactured by Osaka Organic Chemical Industry Co., Ltd.), and "Miramer M500" (manufactured by MIWON Specialty Chemical Co., Ltd.).

[0031] The amount of the (meth)acrylate having a hydroxy group used is usually 0.8 to 2.5 moles, and preferably 0.9 to 2 moles, of the hydroxy group (OH) per mole of the epoxy group in the epoxy compound represented by general formula (1).

[0032] The (meth)acrylate adduct can be obtained by adding an epoxy compound represented by the general formula (1) to a (meth)acrylate having a hydroxyl group. The reaction conditions are not particularly limited, and for example, the temperature is usually about 60 to 120°C (preferably about 80 to 110°C) and the time is about 6 to 15 hours (preferably about 8 to 12 hours).

[0033] In the production of the (meth)acrylate adduct, the above-mentioned organic solvent may be further used. The amount of the organic solvent used is preferably adjusted so that the concentration of the reaction solution is 40 to 70% by weight.

[0034] (Regarding the urethane (meth)acrylate of the epoxy compound) One example of a urethane (meth)acrylate is a product in which an epoxy compound represented by general formula (1) and a diol, a polyisocyanate, and a (meth)acrylate having a hydroxyl group are essential reaction components. More specifically, a product in which a product of an epoxy compound represented by general formula (1) and a diol is reacted with a polyisocyanate and further with a (meth)acrylate having a hydroxyl group can be mentioned.

[0035] Examples of diols include ethylene glycol, 1,2-propanediol (propylene glycol), 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 1,2-heptanediol, 1, Examples of the diols include aliphatic diols such as 5-heptanediol, 1,7-heptanediol, 1,2-octanediol, and 1,8-diol, and alicyclic diols such as 1,2-cyclopentanediol, 1,3-cyclopentanediol, 1,1-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,2-cyclooctanediol, and 1,5-cyclooctanediol. These may be used alone or in combination of two or more.

[0036] The amount of the diol used is usually 0.8 to 1.5 mol, and preferably 0.9 to 1.2 mol, per mol of the epoxy compound represented by the general formula (1).

[0037] Hereinafter, the reaction product of the epoxy compound represented by the general formula (1) and the diol will also be referred to as product (1).

[0038] Examples of the polyisocyanate include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; dicyclohexylmethane-4,4'-diisocyanate, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, norbornene methane diisocyanate, cyclohexane-1,4-diylbis(methylene) diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated tolylene diisocyanate. Examples of the polyisocyanate include alicyclic polyisocyanates such as anate, hydrogenated tetramethyl xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated dimethyl diphenylmethane diisocyanate, and hydrogenated naphthalene diisocyanate; and aromatic polyisocyanates such as xylylene diisocyanate, tolylene diisocyanate, tetramethyl xylylene diisocyanate, diphenylmethane diisocyanate, dimethyl diphenylmethane diisocyanate, and naphthalene diisocyanate. In addition, the polyisocyanate may have any structure of a nurate, adduct, or biuret. These may be used alone or in combination of two or more. Among them, alicyclic polyisocyanates are preferred.

[0039] The amount of polyisocyanate used, expressed as the ratio of the number of isocyanate groups (NCO) of the polyisocyanate to the number of hydroxyl groups (OH) in the product (1), is usually [(NCO) / (OH)]=1.7 to 2.2, and preferably [(NCO) / (OH)]=1.8 to 2.0.

[0040] Hereinafter, the compound obtained by the reaction of the product (1) with a polyisocyanate will also be referred to as product (2).

[0041] Examples of the (meth)acrylate having a hydroxy group include those exemplified in the previous paragraph.

[0042] The amount of the (meth)acrylate having a hydroxy group used, expressed as the ratio of the number of isocyanate groups (NCO) in the product (2) to the number of hydroxy groups (OH) of the (meth)acrylate having a hydroxy group, is usually [(NCO) / (OH)]=0.8 to 1.1, and more preferably 0.9 to 1.0.

[0043] The urethane (meth)acrylate can be obtained, for example, by reacting an epoxy compound represented by general formula (1) with a diol to form product (1), then reacting the product with a polyisocyanate to form product (2), and further reacting the product with a (meth)acrylate having a hydroxy group.

[0044] The reaction conditions for the step of obtaining the product (1) are, for example, usually a temperature of about 60 to 120° C. (preferably about 80 to 110° C.) and a time of about 6 to 15 hours (preferably about 8 to 12 hours). The reaction conditions for the step of obtaining the product (2) and for reacting the obtained product (2) with a (meth)acrylate having a hydroxy group are, for example, usually a temperature of about 50 to 100°C (preferably about 60 to 90°C) and a time of about 0.5 to 3 hours (preferably about 1 to 2 hours).

[0045] The urethane (meth)acrylate can be produced either in the above organic solvent or without a solvent.

[0046] As for the physical properties of the urethane (meth)acrylate thus obtained, for example, the weight average molecular weight is preferably 2000 to 80000. The weight average molecular weight here is a value measured by the GPC method (a polystyrene-equivalent value measured by gel permeation chromatography) (the same applies below).

[0047] Another embodiment of the urethane (meth)acrylate of the present invention is a reaction product of the above-mentioned product (1) with a (meth)acrylate having one isocyanate group.

[0048] Examples of (meth)acrylates having one isocyanate group include isocyanatoalkyl (meth)acrylates such as 2-isocyanatoethyl (meth)acrylate, 3-isocyanatopropyl (meth)acrylate, and 4-butylisocyanatobutyl (meth)acrylate; 2-(2-methacryloyloxyethyloxy)ethyl isocyanate, and 1,1-(bisacryloyloxymethyl)ethyl isocyanate. In addition, commercially available products such as Karenz AOI, Karenz MOI, Karenz MOI-EG, and Karenz BEI manufactured by Showa Denko K.K. can be used. These may be used alone or in combination of two or more.

[0049] The amount of the (meth)acrylate having one isocyanate group used is preferably a ratio of the number of isocyanate groups (NCO) in the (meth)acrylate having one isocyanate group to the number of hydroxyl groups (OH) in the product (1), [(NCO) / (OH)]=0.8 to 1.1, and more preferably 0.9 to 1.0.

[0050] The urethane (meth)acrylate can be obtained by reacting an epoxy compound represented by general formula (1) with a diol to obtain a product (1), and then reacting the product with a (meth)acrylate having one isocyanate group.

[0051] The reaction conditions for the step of obtaining the product (1) are the same as those described in the preceding paragraph. The reaction conditions for reacting the product (1) with a (meth)acrylate having one isocyanate group are, for example, usually a temperature of about 50 to 100°C (preferably about 60 to 90°C) and a reaction time of about 0.5 to 3 hours (preferably about 1 to 2 hours).

[0052] The urethane (meth)acrylate can be produced either in the above organic solvent or without a solvent.

[0053] As for the physical properties of the urethane (meth)acrylate thus obtained, for example, the weight average molecular weight is preferably 1,000 to 40,000.

[0054] Component (B) is a poly(meth)acrylate having three or more (meth)acryloyl groups, and is a component used to provide a cured product exhibiting high hardness.

[0055] Examples of the component (B) include glycerin poly(meth)acrylates such as glycerin tri(meth)acrylate, ethoxylated glycerin tri(meth)acrylate, and propoxylated glycerin tri(meth)acrylate; trialkanol poly(meth)acrylates such as trimethylolmethane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, and alkylene oxide-modified trimethylolpropane tri(meth)acrylate; dimethylolpropane poly(meth)acrylates such as dimethylolpropane tri(meth)acrylate, ethoxylated dimethylolpropane tri(meth)acrylate, propoxylated dimethylolpropane tri(meth)acrylate, and alkylene oxide-modified dimethylolpropane tri(meth)acrylate; pentaerythritol poly(meth)acrylates such as pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, alkylene oxide-modified pentaerythritol tri(meth)acrylate, and alkylene oxide-modified pentaerythritol tetra(meth)acrylate; Dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol tri(meth)acrylate, ethoxylated dipentaerythritol tetra(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, propoxylated dipentaerythritol tri(meth)acrylate, propoxylated di dipentaerythritol poly(meth)acrylates such as pentaerythritol tetra(meth)acrylate, propoxylated dipentaerythritol penta(meth)acrylate, propoxylated dipentaerythritol hexa(meth)acrylate, alkylene oxide-modified dipentaerythritol tri(meth)acrylate, alkylene oxide-modified dipentaerythritol tetra(meth)acrylate, alkylene oxide-modified dipentaerythritol penta(meth)acrylate, and alkylene oxide-modified dipentaerythritol hexa(meth)acrylate; Tripentaerythritol tri(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, ethoxylated tripentaerythritol tri(meth)acrylate, ethoxylated tripentaerythritol tetra(meth)acrylate, ethoxylated tripentaerythritol penta(meth)acrylate, ethoxylated tripentaerythritol hexa(meth)acrylate, ethoxylated tripentaerythritol hepta(meth)acrylate, ethoxylated tripentaerythritol octa(meth)acrylate, propoxylated tripentaerythritol tri(meth)acrylate, propoxylated tripentaerythritol tetra(meth)acrylate tripentaerythritol poly(meth)acrylates such as tripentaerythritol poly(meth)acrylate, propoxylated tripentaerythritol penta(meth)acrylate, propoxylated tripentaerythritol hexa(meth)acrylate, propoxylated tripentaerythritol hepta(meth)acrylate, propoxylated tripentaerythritol octa(meth)acrylate, alkylene oxide-modified tripentaerythritol tri(meth)acrylate, alkylene oxide-modified tripentaerythritol tetra(meth)acrylate, alkylene oxide-modified tripentaerythritol penta(meth)acrylate, alkylene oxide-modified tripentaerythritol hexa(meth)acrylate, alkylene oxide-modified tripentaerythritol hepta(meth)acrylate, and alkylene oxide-modified tripentaerythritol octa(meth)acrylate. Examples of alkylene include ethylene, propylene, butylene, etc. These may be used alone or in combination of two or more. Among them, pentaerythritol poly(meth)acrylates and dipentaerythritol poly(meth)acrylates are preferred because they increase the hardness of the cured product.

[0056] The content of the (B) component, in terms of the solids weight ratio between the (A) component and the (B) component, is preferably (A) / (B)=10 / 90 to 90 / 10, and more preferably 30 / 70 to 80 / 20, in order to balance low moisture permeability and high hardness of the cured product.

[0057] The component (C) is a photoradical initiator that generates radicals by irradiation with active energy rays and serves as the starting point for radical polymerization reactions. Examples of the component (C) include photoradical initiators such as benzoin compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, thioxanthone compounds, and oxime ester compounds, and photosensitizers such as amines and quinones. More specifically, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1- ... propan-1-one, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl]-2-methylpropan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(η 5 -2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 1,2-octanedione 1-[4-(phenylthio)-2-(o-benzoyloxime)], ethanone 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(o-acetyloxime), etc. These may be used alone or in combination of two or more.

[0058] Commercially available products of component (C) include, for example, "Irgacure 651", "Irgacure 184", "Irgacure 1173", "Irgacure 2959", "Irgacure 127", "Irgacure 907", "Irgacure 369", "Irgacure 819", and "Irgacure TPO" (all manufactured by BASF), "Omnirad 651", "Omnirad 184", "Omnirad 1173", "Omnirad 2959", "Omnirad 127", "Omnirad 907", "Omnirad 369", "Omnirad 819", and "Omnirad TPO" (all manufactured by IGM Resins), "Speedcure TPO", and "Speedcure MBP" (all manufactured by Lambson).

[0059] The content of the component (C) is preferably 1 to 10 parts by weight, and more preferably 3 to 8 parts by weight, per 100 parts by weight of the total of the components (A) and (B).

[0060] The curable hard coat resin composition of the present invention may contain a photoacid generator (D) (hereinafter referred to as component (D)). Component (D) is a compound that absorbs light to generate an acid, and is a component that serves as the starting point for the cationic polymerization reaction of epoxy groups.

[0061] Examples of the component (D) include sulfonium salts, iodonium salts, diazonium salts, etc. These may be used alone or in combination of two or more.

[0062] Examples of sulfonium salts include sulfonium phosphates such as triarylsulfonium hexafluorophosphate (e.g., p-phenylthiophenyldiphenylsulfonium hexafluorophosphate, etc.), bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium perfluoroalkylphosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluorophosphate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluorophosphate, 4-phenylcarbonyl-4'-diphenylsulfoniodiphenylsulfide hexafluorophosphate, and diphenyl-4-(phenylthio)phenylsulfonium phosphate; Bis(4-(diphenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(di(4-(2-hydro sulfonium borates such as bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluyl)sulfonio-diphenylsulfide tetrakis(pentafluorophenyl)borate, and 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate; Examples of sulfonium antimonates include triphenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonio-diphenylsulfide hexafluoroantimonate, and 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluoroantimonate. These may be used alone or in combination of two or more.

[0063] Examples of iodonium salts include iodonium phosphates such as diphenyliodonium hexafluorophosphate, diphenyliodonium tetrakis(pentafluorophenyl)borate, di(4-nonylphenyl)iodonium hexafluorophosphate, di(4-t-butylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, and iodonium[4-(4-methylphenyl-2-methylpropyl)phenyl]hexafluorophosphate; iodonium borates such as diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrafluoroborate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate, and tolylcumyliodonium tetrakis(pentafluorophenyl)borate; Examples of the iodonium antimonates include diphenyl iodonium hexafluoroantimonate and di(4-t-butylphenyl) iodonium hexafluoroantimonate. These may be used alone or in combination of two or more.

[0064] Diazonium salts include, for example, diazonium phosphates such as phenyldiazonium hexafluorophosphate; diazonium borates such as phenyldiazonium tetrafluoroborate, phenyldiazonium hexafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate; phenyldiazonium hexafluoroantimonate and other diazonium antimonates. These may be used alone or in combination of two or more.

[0065] Among these (D) components, sulfonium phosphates are preferred because they are easily soluble in organic solvents, the resulting curable hard coat resin composition does not thicken over time, and can be cured quickly, and triarylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium perfluoroalkyl phosphate, and diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate are more preferred.

[0066] Commercially available products of component (D) include, for example, “CPI-100P,” “CPI-101A,” “CPI-200K,” and “CPI-210S” (all manufactured by San-Apro Co., Ltd.), “Kayarad PCI-220,” and “Kayarad PCI-620" (all manufactured by Nippon Kayaku Co., Ltd.), UVI-6990, UVI-6992" (all manufactured by Union Carbide Corporation), ADEKA Optomer SP-150, ADEKA Optomer SP-170" (all manufactured by ADEKA Corporation), CI-5102, CIT-1370, CIT-1682, CIP-1866S, CIP-2048S, CIP-2064S (all manufactured by Nippon Soda Co., Ltd.), DPI-101, DPI-102, DPI-103, DPI-105, MPI-103, MPI-105, Examples of such compounds include BBI-101, BBI-102, BBI-103, BBI-105, BBI-109, BBI-201, TPS-101, TPS-102, TPS-103, TPS-105, MDS-103, MDS-105, DTS-102, DTS-103, and DTS-2000 (all manufactured by Midori Chemical Co., Ltd.), PI-2074 (manufactured by Solvay Japan Co., Ltd.), WPI-113, and WPI-116 (all manufactured by Wako Pure Chemical Industries, Ltd.), and Irgacure 250 (manufactured by BASF).

[0067] The content of the component (D) is preferably 0.1 to 10 parts by weight, and more preferably 0.5 to 5 parts by weight, per 100 parts by weight of the total of the components (A) and (B).

[0068] The curable hard coat resin composition of the present invention may further contain a (meth)acrylate (E) having two or less (meth)acryloyl groups (hereinafter referred to as component (E)). Examples of the component (E) include aliphatic (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, tri-n-decyl (meth)acrylate, n-lauryl (meth)acrylate, n-myristyl (meth)acrylate, n-palmityl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate; alicyclic (meth)acrylates such as cyclohexyl (meth)acrylate, norbornyl (meth)acrylate, isobornyl (meth)acrylate, norbornanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, and tricyclodecane dimethylol di(meth)acrylate; Aromatic (meth)acrylates such as phenyl (meth)acrylate, benzyl acrylate, 2-phenylethyl (meth)acrylate, and nonylphenoxy polyethylene glycol (meth)acrylate; (meth)acrylates having an alkoxyalkyl group, such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, 2-methoxyethoxyethyl (meth)acrylate, and 2-ethoxyethoxyethyl (meth)acrylate; Monoalkylene glycol (meth)acrylates such as ethylene glycol di(meth)acrylate and propylene glycol di(meth)acrylate; polyalkylene glycol (meth)acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; alkoxypolyalkylene glycol (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, and methoxydipropylene glycol (meth)acrylate; Acrylamides such as acrylamide, dimethylacrylamide, diethylacrylamide, and (meth)acryloylmorpholine; (meth)acrylates having an epoxy group, such as glycidyl (meth)acrylate; Dialkylaminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate; Pentaerythritol (meth)acrylates such as pentaerythritol mono(meth)acrylate and pentaerythritol di(meth)acrylate; Dipentaerythritol (meth)acrylates such as dipentaerythritol mono(meth)acrylate and dipentaerythritol di(meth)acrylate; Examples of the di(meth)acrylate include neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.

[0069] These (E) components may be used alone or in combination of two or more. The (E) component reduces the viscosity of the curable hard coat resin composition, making it easier to apply to a substrate film, and also facilitating adhesion between the cured product and the substrate film after curing. On the other hand, when a large amount of the (E) component is blended, the hardness of the cured product is likely to decrease. Therefore, the content of the (E) component is preferably 30% by weight or less, more preferably 15% by weight or less, based on 100% by weight of the total weight of the (A), (B) and (E) components.

[0070] The curable hard coat resin composition of the present invention may further contain inorganic particles (F) (hereinafter referred to as component (F)).

[0071] Examples of the (F) component include silica, alumina, zirconium oxide, titanium oxide, antimony oxide, tin oxide, indium oxide, zinc oxide, etc. The (F) component may be doped with aluminum, phosphorus, fluorine, etc. These may be used alone or in combination of two or more.

[0072] Commercially available products include "TOL-ST," "MEK-ST-40," "MEK-ST-L," "MEK-ST-ZL," "MEK-ST-UP," "MIBK-ST," "CHO-ST-M," "EAC-ST," and "PMA-ST" (all manufactured by Nissan Chemical Industries, Ltd.).

[0073] The component (F) may be a metal oxide having an organic functional group on the surface. The "organic functional group" is a group having at least a carbon atom, such as a methacryloyl group, an acryloyl group, a vinyl group, an epoxy group, an isocyanate group, a urethane group, or an organosiloxane group.

[0074] Commercially available metal oxides having organic functional groups on their surfaces include, for example, "MEK-EC-2130Y", "MEK-AC-2140Z", "MEK-AC-4130Y", "PGM-AC-2140Y", "PGM-AC-3140Y", "PGM-AC4130Y", "MIBK-SD", "MIBK-SD-L" (manufactured by Nissan Chemical Industries, Ltd.), "NANOBYK-3603", "NANOBYK-3610", Examples include "NANOBYK-3650", "NANOBYK-3652" (manufactured by BYK Japan Co., Ltd.), "ALMIBK30WT%-H06", "SIRMIBK15ET%-H24", "SIRMIBK15ET%-H83" (manufactured by CIK Nanotech Co., Ltd.), "ELECOM-V8802", "ELECOM-V8803", and "ELECOM-V8804" (manufactured by JGC Catalysts and Chemicals Co., Ltd.).

[0075] The average primary particle size of component (F) is preferably about 5 to 100 nm, and more preferably about 10 to 50 nm. The method for measuring the average primary particle size is not particularly limited, and examples thereof include a light scattering method.

[0076] When the (F) component is used as a component of the curable hard coat resin composition, its content is preferably 5 to 50% by weight, and more preferably 10 to 30% by weight, based on 100 parts by weight of the total of the (A) and (B) components, in order to achieve a balance between low moisture permeability and high hardness of the cured product.

[0077] The curable hard coat resin composition of the present invention may further contain an organic solvent.

[0078] The organic solvent is not particularly limited, and examples thereof include aromatic hydrocarbons such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, isooctane, and n-decane; alicyclic hydrocarbons such as cyclohexane; esters such as ethyl acetate, propyl acetate, n-butyl acetate, s-butyl acetate, t-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-methoxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, 1-methoxypropyl acetate, and methyl benzoate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, cyclohexanone, and methylcyclohexanone; and dimethyl carbonate. Examples of the organic solvent include carbonates such as ethyl ether, diethyl carbonate, and ethylene carbonate; non-cyclic ethers such as diisopropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether; cyclic ethers such as tetrahydrofuran, 1,3-dioxolane, and 1,4-dioxane; monohydroxy ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether; and alcohols such as methanol, ethanol, n-propanol, 2-propanol, n-butanol, isobutanol, s-butanol, and t-butanol. When an organic solvent is used, the content thereof is preferably adjusted so that the solid content concentration of the curable hard coat resin composition is 10 to 50% by weight.

[0079] The curable hard coat resin composition of the present invention may further contain additives such as a surface conditioner, a surfactant, an ultraviolet absorber, an antioxidant, a light stabilizer, a silane coupling agent, colloidal silica, an antifoaming agent, a wetting agent, a rust inhibitor, and a leveling agent.

[0080] The curable hard coat resin composition of the present invention can be obtained by mixing the components (A), (B), and (C), and optionally the components (D), (E), and (F), an organic solvent, and the above-mentioned additives. The mixing means and mixing order are not particularly limited.

[0081] The cured product of the present invention is obtained by curing the above-mentioned curable hard coat resin composition.

[0082] The cured product of the present invention is not particularly limited, and can be obtained, for example, by applying the curable hard coat resin composition to a substrate and irradiating the substrate with active energy rays.

[0083] Examples of the substrate film include cellulose ester films such as diacetyl cellulose film, triacetyl cellulose film, acetyl propyl cellulose film, and acetyl butyl cellulose film; polyvinyl alcohol films such as polyvinyl alcohol film and ethylene vinyl alcohol film; cellophane, polyamide film, and polylactic acid film. The substrate may be one with light or heavy release properties, and may be untreated or plasma-treated.

[0084] The substrate may be subjected to a release treatment to facilitate peeling from the cured layer. If peeling is easy, the release treatment is not particularly necessary, but to facilitate peeling, a release layer made of melamine resin, silicone resin, fluororesin, cellulose derivative, urea resin, polyolefin resin, or paraffin resin may be laminated. These substrates may be used alone or in combination of two or more.

[0085] The thickness of the substrate is not particularly limited, and is usually about 12 to 500 μm, and preferably 25 to 200 μm.

[0086] The coating method is not particularly limited, and examples thereof include an applicator, a bar coater, a roll coater, a knife coater, a gravure coater, a spray coater, a comma coater, a lip coater, gravure printing, screen printing, etc. The amount of the curable hard coat resin composition to be applied is also not particularly limited, and the coating is usually performed so that the film thickness of the cured product after irradiation is about 1 to 50 μm.

[0087] After coating, the coating may be irradiated with active energy rays, or the coating may be dried by heating to partially cure it. When drying by heating, it is preferable to dry the coating at a temperature of about 40 to 100° C. for 20 seconds to 10 minutes.

[0088] The active energy rays are not particularly limited, and examples thereof include light rays such as ultraviolet rays, infrared rays, and visible light rays, electron beams, X-rays, α rays, β rays, γ rays, neutron rays, etc. In the present invention, light rays are preferred, and ultraviolet rays are more preferred.

[0089] The light source of the ultraviolet ray is not particularly limited, and examples thereof include a xenon lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a chemical lamp, an electrodeless lamp, an LED lamp, etc. The cumulative dose of the ultraviolet ray and the conveying speed are also not particularly limited, and the cumulative dose is usually 100 to 3000 mJ / cm. 2 The conveying speed is usually about 5 to 50 m / min. After the ultraviolet ray irradiation, the coating may be heated as necessary for complete curing.

[0090] The laminate of the present invention has a layer of the cured product on at least one surface of a substrate. The substrate and the curing method are the same as those described above. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples, but is not limited thereto. Unless otherwise specified, all "parts" and "%" are by weight.

[0092] <About component (A)> As the component (A-1), a compound represented by the following formula (2) (product name: "DE-103", manufactured by ENEOS Corporation) was used (hereinafter referred to as DE-103).

[0093] [ka]

[0094] Synthesis Example 1 Into a three-neck flask equipped with a stirrer, a thermometer, and a reflux condenser, 42.4 parts (1 mole) of DE-103, 17.6 parts (2 moles) of acrylic acid, 40.0 parts of methyl isobutyl ketone, 0.2 parts of triphenylphosphine, 0.1 parts of hydroquinone monomethyl ether, and 0.03 parts of phenothiazine were added and stirred at 105° C. for 8 hours. It was confirmed that the acid value was 5.0 mgKOH / g or less, and a solution of acrylic acid adduct (A-3) with a solid content concentration of 60% was obtained.

[0095] Synthesis Example 2 Into a three-neck flask similar to that of Synthesis Example 1, 16.4 parts (1 mole) of DE-103, 43.6 parts (2 moles) of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name: "Viscoat #300", hydroxyl value: 121.0 mgKOH / g, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 40.0 parts of methyl isobutyl ketone, 0.2 parts of triphenylphosphine, 0.1 parts of hydroquinone monomethyl ether, and 0.03 parts of phenothiazine were added and stirred at 105°C for 15 hours to obtain a solution of a (meth)acrylate adduct (A-4) with a solid content concentration of 60%.

[0096] Synthesis Example 3 Into a three-neck flask similar to that in Synthesis Example 1, 4.2 parts (1 mole) of DE-103, 1.5 parts (2 moles) of ethylene glycol, 3.8 parts of methyl isobutyl ketone, 0.02 parts of triphenylphosphine, 0.01 parts of hydroquinone monomethyl ether, and 0.003 parts of phenothiazine were added and stirred at 105° C. for 15 hours. Next, 9.4 parts (4 moles) of hydrogenated xylylene diisocyanate (H6XDI), 6.3 parts of methyl isobutyl ketone, and 0.002 parts of tin octylate were added, and the mixture was stirred at 80°C for 2 hours. Then, 44.9 parts (4 moles) of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name: "Viscoat #300", hydroxyl value: 121.0 mg KOH / g, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 0.06 parts of tin octylate, and 29.9 parts of methyl isobutyl ketone were added, and the mixture was allowed to react until the residual isocyanate group was 0.1% or less, thereby obtaining a solution of urethane (meth)acrylate (A-5) with a solid content concentration of 60%.

[0097] Example 1 80 parts of DE-103, 20 parts of dipentaerythritol polyacrylate (product name: "NK Ester A-DPH", manufactured by Shin-Nakamura Chemical Co., Ltd.), 5 parts of 1-hydroxycyclohexyl phenyl ketone (photoradical initiator, product name: "Omnirad 184", manufactured by IGM Resins BV), and 3 parts of triarylsulfonium salt (product name: "CPI-210S", manufactured by San-Apro Co., Ltd.) were mixed and stirred until dissolved to prepare a curable hard coat resin composition.

[0098] Examples 2 to 12, Comparative Examples 1 to 4 The components were mixed according to the compositions shown in Table 1 to prepare respective curable hard coat resin compositions.

[0099] (Laminate) Triacetyl cellulose film (product name: "FT TD60ULP", Fujifilm Corporation, moisture permeability: 500g / m 2 Each curable hard coat resin composition was applied to the substrate (24 h, thickness: 60 μm) using a bar coater so that the film thickness after curing would be 7 μm, and then dried at 80° C. for 1 minute. Next, a high-pressure mercury lamp (product name: “UBT-080-7A / BM”, manufactured by Multiply Co., Ltd.) was used to irradiate the substrate with an accumulated dose of 200 mJ / cm 2 2 The laminate was obtained by irradiating with light at 400 nm.

[0100] (moisture permeability) Using each laminate, the moisture permeability test was performed in accordance with the JIS Z 0208 moisture permeability test method (cup method). 2 The number of grams of water vapor passing through the fabric per 24 hours was measured. The lower the number of grams, the lower the moisture permeability. 2 / 24h or less was considered good.

[0101] (Pencil hardness) The hardness of the cured product of each laminate was measured by a pencil scratch test with a load of 750 g in accordance with JIS K 5600-5-4, and was evaluated according to the following criteria. (Evaluation Criteria) ◎: Pencil hardness is 2H or more ○: Pencil hardness is F or more and H or less ×: Pencil hardness is HB or less

[0102] [Table 1] *1: Indicates the content of epoxy compound and poly(meth)acrylate per 100 parts by weight of total solid content.

[0103] The symbols in Table 1 represent the following compounds. <Epoxy compounds and their derivatives> A-1: Epoxy compound represented by formula 2 (product name: "DE-103", manufactured by ENEOS Corporation) A-2: Epoxy compound represented by formula 3 (product name: "DE-102", manufactured by ENEOS Corporation) A-3: Acid adduct of Production Example 1 A-4: Acrylate adduct of Preparation Example 2 A-5: Urethane acrylate of Production Example 3 G-1: Epoxy compound represented by formula 4 (product name: "THI-DE", manufactured by ENEOS Corporation) <Poly(meth)acrylate> B-1: Dipentaerythritol polyacrylate, product name: "NK Ester A-DPH", manufactured by Shin-Nakamura Chemical Co., Ltd. B-2: A mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate, product name: "NK Ester A-TMM-3L", manufactured by Shin-Nakamura Chemical Co., Ltd. E-1: Tricyclodecane dimethanol diacrylate, product name: "NK Ester A-DCP", manufactured by Shin-Nakamura Chemical Co., Ltd. <Photoradical initiator> C-1: 1-Hydroxycyclohexyl phenyl ketone, trade name: "Omnirad 184", manufactured by IGM Resins <Photoacid generator> D-1: Diphenyl[4-(phenylthio)phenyl]sulfonium perfluoroalkylphosphate, product name: "CPI-210S", manufactured by San-Apro Co., Ltd. <Inorganic particles> F-1: Methacryloyl-modified silica, product name: "MEK-AC-2140Z", average primary particle size: 10-15 nm, manufactured by Nissan Chemical Co., Ltd.

[0104] [ka]

[0105] [ka]

[0106] [ka]

Claims

1. The composition comprises an epoxy compound represented by general formula (1) and / or a derivative thereof (A), a poly(meth)acrylate having three or more (meth)acryloyl groups (B), and a photoradical initiator (C), The derivative is any one of an α,β-unsaturated carboxylic acid adduct of the epoxy compound, a (meth)acrylate adduct having a hydroxy group of the epoxy compound, and a urethane (meth)acrylate of the epoxy compound. 【Chemistry 1】 (In formula (1), the dashed line means no bond or a carbon-carbon-carbon bond.)

2. 2. The curable hard coat resin composition according to claim 1, wherein the component (B) comprises at least one selected from the group consisting of pentaerythritol poly(meth)acrylate, dipentaerythritol poly(meth)acrylate, and tripentaerythritol poly(meth)acrylate.

3. 3. The curable hard coat resin composition according to claim 1, wherein the ratio of the components (A) and (B) used is, by solid weight, (A) / (B)=10 / 90 to 90 / 10.

4. The curable hard coat resin composition according to any one of claims 1 to 3, further comprising a photoacid generator (D).

5. 5. The curable hard coat resin composition according to claim 1, further comprising a (meth)acrylate (E) having two or less (meth)acryloyl groups.

6. The curable hard coat resin composition according to any one of claims 1 to 5, further comprising inorganic particles (F).

7. A cured product of the resin composition for curable hard coat according to any one of claims 1 to 6.

8. A laminate having the cured product according to claim 7 on at least one surface of a substrate.

Citation Information

Patent Citations

  • Surface protective sheet

    JP1997290491A

  • Photosensitive resin composition and insulating film for touch panel

    JP2012116975A

  • Photocurable resin composition for forming protective layer, cured product of the same, and optical film

    JP2016166307A

  • Curable composition

    JP2019196428A

  • Curable composition and cured product thereof

    JP2020172574A